Lipomatous/Extensively Vacuolated Ependymoma with Signet-Ring Cell-Like Appearance: Analysis of a Case with Extensive Literature Review - Miguel Fdo. Salazar; Martha Lilia Tena-Suck; Alma Ortiz-Plata; Citlaltepetl Salinas-Lara; Daniel Rembao-Bojórquez (Hindawi Limited, 2017)
"Lipomatous" and "extensively vacuolated" are descriptive captions that have been used to portray a curious subset of ependymomas distinctively bearing cells with a large vacuole pushing the nucleus to the periphery and, thus, simulating a signet-ring cell appearance. Here, we would like to report the first ependymoma of this kind in a Latin American institution. A 16-year-old boy experienced cephalea during three months. Magnetic resonance imaging scans showed a left paraventricular tumour which corresponded to anaplastic ependymoma. Intriguingly, it was also composed of cells with single or multiple hollow cytoplasmic vacuoles sometimes giving a signet-ring cell-like configuration. Immunolabeling of these showed membrane positivity for GFAP, PS100, and CD99, while Ki-67 expression was null. Ultrastructural examination of retrieved paraffin-embedded tissue showed the presence of scarce microlumina filled with microvilli but failed to demonstrate any content in such optically empty vacuoles as only scant granulofibrillary debris was observed. A schism prevails at present regarding these unusual morphological variants, being either "lipomatous" or "vacuolated" based mainly on the EMA immunoprofile. This, however, is a misappropriate approaching. Could it be that perhaps we are dealing with the same histopathological entity or it may simply happen that fixation and artefacts cannot allow for their proper identification?